Long-Term Effects of Moderate Concussive Brain Injury During Adolescence on Synaptic and Tonic GABA Currents in Dentate Granule Cells and Semilunar Granule Cells - Gupta, Akshay; Dovek, Laura; Proddutur, Archana; Elgammal, Fatima S.; Santhakumar, Vijayalakshmi (Frontiers in Neuroscience, 2022)
Progressive physiological changes in the hippocampal dentate gyrus circuits following traumatic brain injury contribute to temporal evolution of neurological sequelae. Although early posttraumatic changes in dentate synaptic and extrasynaptic GABA currents have been reported, whether they evolve over time and remain distinct between the two projection neuron classes, granule cells and semilunar granule cells, has not been evaluated. We examined long-term changes in tonic GABA currents and spontaneous inhibitory postsynaptic currents (sIPSCs) and in dentate projection neurons three month after moderate concussive fluid percussion injury (FPI) in adolescent rats. Granule cell tonic GABA current amplitude remained elevated up to one month after FPI, but decreased to levels comparable to age-matched controls by three months postinjury. Granule cell sIPSC frequency, which we previously reported to be increased one week after FPI, remained higher than in age-matched controls at one month and was significantly reduced three months after FPI. In semilunar granule cells tonic GABA current amplitude and sIPSC frequency was not different from controls three months after FPI which contrasts with decreases observed one week after injury. The switch in granule cell inhibitory inputs from early increase to subsequent decrease could contribute to the delayed emergence of cognitive deficits and seizure susceptibility after brain injury.